Responses Triggered by the Immune System in Hypertensive Conditions and Repercussions on Target Organ Damage: A Review - da Silva, Carlos Henrique Nascimento Domingues; Guedes, Idrys H. L.; de Lima, Jefferson Carlos Santos; Sobrinho, João Marcelo Duarte Ribeiro; dos Santos, Angela A. (Current Cardiology Reviews, 2023)
Background: Hypertension is a chronic, multifactorial clinical condition characterized by sustained high blood pressure levels. It is often associated with functional-structural alterations of target organs, which include heart, brain, kidneys, and vasculature. Objective: This study highlights the recent correlation between the immune system and hypertension and its repercussions on target-organ damage. Methods: The descriptors used for the search of the study were
Keywords: immune system